Interaction of silica colloid and iron oxide nanoparticles with mice bone marrow derived-dendritic cells - Zamry , Anes Ateqah (2017)
Dendritic cells (DCs) are an important component of innate immunity, which modulate the adaptive immunity. DCs act as a key sentinel in maintaining our immune homeostasis and as professional antigen-presenting cells (APCs). DCs have been targeted in various medical applications such as in vaccine research and immunotherapeutic development due to the ability of activated DCs in initiating the innate immune response and consequently trigger the adaptive immune response. The use of nanoparticles (NPs) have shown a great potential in activating bone marrow derived-dendritic cells (BMDCs) that lead to DCs maturation, which in turn will induce the innate and adaptive immune responses. The aims of this study is to produce and characterise two types of NPs namely silica colloid NPs and iron oxide NPs, to determine the morphology and activation status of BMDCs upon exposure to NPs and also to determine the uptake and intracellular localisation of both NPs by BMDCs. The spherical silica colloid and iron oxide NPs were successfully synthesised and characterised with the hydrodynamic size of 174.7 nm ± 2.20 and 214.0 nm ± 2.85, respectively.Then, the morphology of generated DCs derived from the bone marrow stem cells of female BALB/c mice after 24 hours exposure to 25 ng/mL silica colloid and iron oxide NPs were observed through a scanning electron microscope imaging, whereby the electron microscopy showed that the BMDCs internalised the NPs into their enclosed membrane. The activation status of BMDCs upon exposure to silica colloid and iron oxide NPs were determined through flow cytometry analyses, in which the expression of DCs surface markers; MHCII, CD86 and CD11c were enhanced in the BMDCs that were exposed to the silica colloid and iron oxide NPs as compared to the BMDCs without NPs exposure. Furthermore, the intracellular localisation of NPs into BMDCs was confirmed by confocal laser scanning microscope, where NPs were deposited inside the membrane of the cells indicating the uptake of NPs into the BMDCs. Besides, the concentration of proinflammatory cytokine IL-12p70 in the cell culture supernatant of BMDCs exposed to silica colloid and iron oxide NPs were higher than the BMDCs that do not exposed to NPs. Whilst these results revealed several promising aspect of the silica colloid and iron oxide NPs as a future candidate for an effective therapeutic applications, these findings warrant further research before they can be integrated into the development of future drug delivery agent, vaccine and immunotherapeutic treatments.